Interaction of university students with educational content in the conditions of information educational environment - E. G. Belyakova; I. G. Zakharova (Образование и наука)
Introduction. Modern society is developing dynamically and its information resources are constantly replenished. Today, the role of students as subjects of professional development, who productively interact with educational content and the role of their teachers as intermediaries and “navigators” in this interaction, is significantly increasing. In this connection, there is the problem of students’ readiness to form the content of their education through the selection and use of resources of the information educational environment (IEE). The urgency of the problem is enhanced in the context of the integration of formal and non-formal education, its personalisation in an open information environment and the individualisation of education through the practice of individual educational trajectories.The aim of the present research was to identify the current state of interaction of university students with educational content.Methodology and research methods. The questionnaire method was the basic tool of the empirical research. The authors’ questionnaire was used to identify the nature of students’ preferences in choosing and using educational content and to correlate the findings with the opinion of teachers. The K-means method was employed to analyse data, systematise it and cluster the respondents.Results and scientific novelty. The most and least actively used by students types of educational content are identified. The relevance of each type of various educational content is rated; its forms of students’ work are established. The choice of content for students is determined by their training profile (humanities and nonhumanities). In addition, on the basis of a comprehensive qualitative and quantitative data analysis, the typological heterogeneity of students in the information educational environment is proved. Data clustering, based on the established indicators of involvement level of educational resources by respondents, allowed the authors to identify typological groups among students (“passive”, “active”, “advanced”, “professionally-oriented” and “humanities”), differing in ways and, apparently, in the selection goals of educational content. The representation of these typological groups at different stages of university education (bachelor or master degree programmes in IT and pedagogical specialties) is observed. Productive and adaptive motivation of students for the use of educational content has been identified. It is noted that students evaluate their activity in interaction with educational content and the productivity of motivation is much higher than their teachers estimate. The obtained results allow the authors to say that the personalisation of the information educational environment should be built in order to the requests of student groups with different interests and motivation for using educational content. To collect necessary information on the peculiarities of activity of future specialists under the personification of access to content and communication in the information educational environment, it is necessary to use modern Big Data tools and search for additional methodological resources when organising vocational education.Practical significance. The research materials and results can become the basis for the development of recommendations on support and development of activity of students’ interaction with educational content. Moreover, the materials of research can contribute to change the meaning of this interaction, which has to consist in understanding by students of own education as individual vocational self-development.